(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the mean change in VAS score after intra-articular injection of Hyaluronic acid and Steroids in patients with initial stages of knee osteoarthritis. Study Design: Randomized controlled trail study. Place and Duration of Study: This study was conducted at the department of Orthopedics, BVH Bahawalpur from September 2017 to February 2018. Materials and Methods: To compare the mean change in VAS score after intra-articular injection of Hyaluronic acid and Steroids in patients with initial stages of knee osteoarthritis Results: The mean age in group A was 59.55 ± 7.60 years and group B 59.37 ± 8.26 years. Out of these 80 patients, 52 (65.0%) were females and 28 (35.0%) males with 1.85:1 female-male ratio. Mean pre-treatment VAS score in group A was 6.30 ± 1.38 while in group B was 5.95 ± 1.50. Mean post-treatment VAS score in group A was 4.48 ± 1.26 while in group B was 1.60 ± 0.93. Mean reduction in VAS score in group A was 1.82 ± 0.12 while in group B was 4.35 ± 0.57. Conclusion: We recommend hyaluronic acid in patients with initial stages of knee OA because significant reduction in mean VAS score (at 6 months) observed with intra-articular hyaluronic acid as compared to corticosteroid use.